Aromatic self-assembled monolayers with pentafluoro-λ6-sulfanyl (- SF5) termination: molecular organization and charge transport properties - Liu, Yangbiao; Zeplichal, Marc; Katzbach, Sonja; Wiesner, Adrian; Das, Saunak; Terfort, Andreas; Zharnikov, Michael (Nano research, 2023)
A series of molecules with oligophenylene backbone, thiolate anchoring group, and pentafluoro-λ6-sulfanyl (−SF5) tail group was synthesized and used as precursors to form self-assembled monolayers (SAMs) on Au(111) substrates. The resulting SAMs feature dense molecular packing, upright molecular orientation, and chemically homogeneous SAM-ambient interface, comprised entirely of the −SF5 moieties. These SAMs exhibit exceptional wetting and electrostatic properties, showing advancing water contact angles up to 103° and work function values up to 5.96 eV—probably the highest values reported for any aromatic monolayers on gold. They also feature a comparably low value of the tunnelling decay coefficient (0.38 ± 0.07 Å−1), typical of oligophenylene backbone, which is not affected by the introduction of the −SF5 group. The latter also hardly affects the current densities at a specific bias compared to analogous monolayers with other electronegative tail groups. The superior electrostatic and good charge transport properties of the designed, SF5-terminated SAMs make them potentially useful for interface engineering in organic electronics and photovoltaics.
Veröffentlicht: 04. Februar 2023
Im Titel ist "lambda" als griechischer Buchstabe dargestellt
Im Titel ist die Zahl 6 hoch- und die Zahl 5 tiefgestellt
Gesehen am 27.09.2023